Contractual balance on lease agreement in shopping center: control of unfair terms and the promise of flagship store - Konder, Carlos Nelson (2016)
This paper analyses the contractual balance principle in business-to-business contracts; thus, studying in detail the asymmetry of bargaining power between different parties, which can be foreign to a consumerist relationship. This study also explores the case of a lease agreement that happened between a tenant-shop and a mall owner. Therefore, with the already mentioned example, we aim to discuss the importance and relevance of the different bargaining strength between parties - in particularly, as this specific anchor store had a promise clause, which faithfully falls within the equilibrium of the agreed contract.